The Influence of Financial Decisions and Business Strategy on Company Value with Financial Performance as a Mediation Variable Please create a background - Hani Krisnawati; Y. Sutomor; Sukirman; Muhammad Nurul Anwar (LP2M IAIN Palopo, 2026)
This study aims to analyze the effect of financial decisions and business strategy on firm value with financial performance as a mediating variable. The proposed hypotheses suggest that financial decisions and business strategy have both direct and indirect effects on firm value through financial performance. This research employs a quantitative approach with an explanatory design. The sample consists of companies listed on the Indonesia Stock Exchange during the 2020–2024 period, selected using purposive sampling. The data used are secondary data obtained from annual financial reports. The variables include financial decisions, business strategy, financial performance, and firm value. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results indicate that financial decisions and business strategy have a positive and significant effect on firm value. In addition, both variables positively influence financial performance. Financial performance also has a positive effect on firm value and partially mediates the relationship between financial decisions and business strategy on firm value. The implications suggest that integrating financial policies with business strategy is crucial for enhancing firm value. These findings provide practical insights for managerial decision-making and offer directions for future research to expand the model with additional variables or different contexts